Factors Influencing Mathematics Achievement among Saudi Students Compared to High-Performing Countries in TIMSS - Alhisony, Mohammed Humaydan; Alharbi, Mohammed Sant (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to identify the most significant factors influencing mathematics achievement related to teachers and students, based on the performance of fourth and eighth-grade students in countries that demonstrated positive outcomes in the 2019 Trends in International Mathematics and Science Study (TIMSS). The study employed a descriptive research methodology, with the sample comprising all students and schools participating in the selected countries. The findings revealed that the most influential factors in mathematics achievement were as follows: Regarding the teacher-related factors, the most significant was the academic qualification across all high-performing countries for both fourth and eighth grades. Concerning student-related factors, student confidence in mathematics and absenteeism were the most impactful on mathematics achievement among fourth and eighth graders in all countries, except for Sweden, where, in addition to student confidence in mathematics, learning and teaching challenges were also significant factors. The study key recommendations included focusing on the preparation and training of successful teachers to meet contemporary educational demands. It also suggested developing contemporary educational perspectives to employ modern teaching strategies and methods to enhance and update the curriculum structure and its scientific content. Furthermore, it advocated for benefiting from successful international educational policies and experiences across various domains of the educational process.
Keywords: Achievement; Mathematics; Positive Performance; TIMSS